Interactive Learning for Teaching Physics Subjects at MA Nurul Huda Talang, Saronggi, Sumenep, Madura - Yuniar Mughayyirah; Nadziratul Ulya; Imam Anas Mubarok (International Journal of Educational Evaluation and Policy Analysis, 2025)
Physics is a subject that students are less interested in because it has a high level of difficulty in understanding, so to increase students interest and sympathy for physics, learning media that is interesting and not monotonous is needed. However, the reality in the field is that there are still very few teachers who have the skills and abilities to develop interesting learning media such as interactive learning media such as "Interactive Learning". Learning with Interactive Learning is believed to be able to stimulate good and efficient student development. The objectives of this activity include producing interactive macromedia flash learning media that is easy to learn and to find out the advantages of macromedia flash interactive learning media when compared to power point. So with this activity it is hoped that it can increase students abilities and interest in teaching and learning activities in Physics subjects at MA Nurul Huda Talang, Saronggi, Sumenep, Madura. The results of this service prove that the existence of interactive learning for teaching Physics subjects at MA Nurul Huda Talang, Saronggi, Sumenep has a positive impact and is able to increase students interest and abilities in the process of teaching and learning Physics subjects. Apart from that, the interactive learning activity has provided motivation to Physics teachers at MA Nurul Huda Talang, Saronggi, Sumenep, Madura to further improve their abilities in creating more interesting and innovative teaching materials.